Synthesis of 2,3-Bis(2-benzothiazolyldisulfanyl)-1-propanol - Padhy, A.K.; Pati, Anita; Nanda, S.P.; Dey, R.K. (Asian Journal of Chemistry, 2010)
The TLC monitored reaction of 2,2'-dithiobisbenzothiazole with 2,3-dithiopropanol resulted in the formation of unsymmetrical disulfides i.e., 2,3-bis(2-benzothiazolyldisulfanyl)-1-propanol (3). The molecule is characterized using proton NMR study. The molecular model study of the compound 3 reveals the proximity of the -OH proton to the nitrogen atom of the benzothiazole ring providing the probable hydrogen bond formation which is further confirmed by the study of hydrogen-deuterium exchange reaction.